Dielectric spectra of thawed and frozen wet organic Arctic soils - Savin, Igor; Mironov, Valery (Zenodo, 2020)
The submitted files contain laboratory data dielectric spectra measurements for six Arctic organic soils. The data are presented in the frequency dependences form of the refractive index and normalized attenuation coefficient obtained at various moistures and temperatures of soil samples.